Program Latihan dan Komunikasi Pemenuhan Activity Daily Living Pasien Pasca Stroke dengan Gangguan Kognitif - Sa'pang, Fransiska Anita Ekawati Rahayu; Sambo, Mery; Soharto, Thomas; Ganut, Felisima; Gau, Meliana; Anugrah, Dwi (Abdimas Universal, 2025)
Cognitive impairment is one of the side effects that often occurs in stroke patients which will reduce the patient's ability to fulfill the daily needs of Activity Daily Living (ADL) that can cause a decrease in the quality of life so that it causes healing to be long, the length of hospitalization extends, becomes an economic and social burden on the families. The physical and cognitive disabilities experienced also cause various nursing problems. It is very important for nurses to recognize the occurrence of cognitive impairment in post-stroke patients starting from assessment and if there is cognitive impairment, so that nurses can intervene with exercise therapy and communication in cognitive impairment of stroke patients. The method used is training with evaluation in the form of pre and post tests. The material provided is an assessment of cognitive impairment and a communication training program for ADL fulfillment in post-stroke patients with cognitive impairment consisting of 2 two sessions and followed by a question and answer discussion session and role play using digital media. The results showed an increase in knowledge and skills of nurses in assessing cognitive impairment and training and communication of ADL fulfillment in post-stroke patients with cognitive impairment.